Legitimating Extremism: A Taxonomy of Justifications for Political Violence - VandenBerg, Robert J. (Terrorism and political violence, 2021)
Terrorism is an inherently communicative enterprise in that it attempts to convey messages using violent means. Furthermore, the effective use of rhetoric is fundamental to the sustainment of militant campaigns. Nevertheless, the literature on terrorism currently lacks a comprehensive blueprint for analyzing terrorist discourse. This paper proposes a framework for classifying narrative frames that serve to justify acts of political violence. Drawing on the social movements literature, it utilizes the jihadist organizations Al Qaeda and the self-proclaimed Islamic State as primary examples to show how militants utilize defensive, moralistic, legalistic, imperialistic, and apocalyptic framing to legitimate acts of terrorism. It also demonstrates how these same categories can be applied to extremists animated by ideologies other than jihadism.